DEVELOPING AND IMPLEMENTING AN ORGANIZATIONAL COMMITMENT SCALE FOR EMPLOYEES IN BASRA YOUTH AND SPORTS DIRECTORATE - Alrikabi , Husham Abbas Neamah (Universitas Negeri Jakarta, 2026)
Background. Commitment, obedience, sincerity, and loyalty are among most important factors that have become a primary concern for management of organizations responsible for maintaining them in a healthy and sound state that enables their survival and continuity. Objectives. This study aimed to develop and apply an organizational commitment scale to employees of Basra Youth and Sports Directorate. Method. The researcher used a descriptive survey methodology, and study instrument was an organizational commitment scale consisting of 20 items distributed across three domains: affective commitment, continuity commitment, and ethical commitment. research sample consisted of 215 employees of Basra Youth and Sports Directorate. study was divided into three groups: a survey sample of 7, a construction sample of 116 workers, and a main application sample of 92 individuals. Results. Results showed that employees at Basra Youth and Sports Directorate possess a strong emotional commitment to their institution, demonstrated by their feelings of pride, honor, and loyalty. Emotional commitment is considered a crucial factor in achieving organizational commitment. high level of ethical commitment among Basra Youth and Sports Directorate employees stems from their adherence to principles, values, and ethics they were raised with, and their awareness of importance of their moral and ethical obligations to their institution. Conclusion. Study's most important conclusion is development and application of an organizational commitment scale for employees at Basra Youth and Sports Directorate. It also recommends promoting a culture of organizational commitment among Basra Youth and Sports Directorate employees, based on dimensions of organizational commitment.